An Integrative Approach for the Characterization of Plant-Pathogenic Streptomyces spp. Strains Based on Metabolomic, Bioactivity, and Phylogenetic Analysis - Croce, Valentina; López-Radcenco, Andrés; Lapaz, María Inés; Pianzzola, María Julia; Moyna, Guillermo; Siri, María Inés (Frontiers in Microbiology, 2021)
Actinomycetes are generally recognized as a diverse group of gram-positive, mycelium-forming, soil bacteria that play an important role in mineralization processes and plant health, being Streptomyces the most well-known genus from this group. Although plant pathogenicity is a rare attribute in this genus, some species have significant impact worldwide due to their ability to cause important crop diseases such as potato common scab (CS). In this work, an integrative approach was applied to investigate the pathogenic potential of Streptomyces spp. isolates obtained from a local collection of actinomycetes isolated from potato fields. Secretion of phytotoxic compounds was verified in most pathogenic strains from our collection (27 out of 29), and we followed metabolomic analysis to investigate those phytotoxins. We first evaluated the production of the known phytotoxins thaxtomin A (TXT) and desmethylmensacarcin (DMSN) in phytotoxic Streptomyces spp. by HPLC analysis, resulting in 17 TXT and 6 DMSN producers. In addition, NMR-based metabolomic models were able to classify strains according to their phytotoxicity, and metabolomic data was also used to infer chemotaxonomy within pathogenic species. A correlation between phylogeny and the production of distinct phytotoxins was found, supporting the idea that there are “species specific” metabolites produced by this genus. The recently discovered polyketide DMSN was associated unequivocally with S. nivescabiei strains and was not produced by other species in the growth conditions employed. Two S. niveiscabiei and two S. puniciscabiei phytotoxic strains that did not produce TXT nor DMSN, suggest the production of other kind of metabolites involved in phytotoxicity and allowed the prioritization of these strains for further chemical studies. Indeed, we found two S. nivescabiei strains whose supernatants were not phytotoxic in the radish assay, suggesting other pathogenic mechanisms involved. We believe our work will be useful to help understand relations between metabolites and phylogenetic clades within actinomycetes.